Characteristic strengthening mechanisms in body-centered cubic refractory high/medium entropy alloys. (1st July 2023) - He, Qian; Yoshida, Shuhei; Tsuji, Nobuhiro
Abstract: The present work reports characteristic strengthening mechanisms of HfNbTaTi, HfNbTiZr, HfNbTi, HfTaTi, and NbTiZr equi-atomic refractory medium entropy alloys (RMEAs). The alloys were processed by high-pressure torsion and subsequent annealing to obtain microstructures with average grain sizes ranging from several hundred nanometers to several tens of micrometers. Their mechanical properties were evaluated by tensile tests at room temperature. Precise Hall–Petch relationships of the RMEAs were acquired based on the tensile yield strength data. Small slopes of the Hall–Petch relationships and weak grain refinement strengthening were clarified to be attributed to their low elastic modulus. In addition, the friction stresses in the RMEAs were higher than those of conventional BCC metals and alloys. By comparing the experimental data and a theoretical model, it was suggested that interaction between severe lattice distortion and elastic field of edge dislocations can largely contribute to the high friction stress of the RMEAs at room temperature. Graphical abstract: Image, graphical abstract